Fruit structure of 12 Turkish endemic Tripleurospermum Sch. Bip. (Asteraceae) taxa and its taxonomic implications - Inceer, Huseyin; Bal, Murat; Ceter, Talip; Pinar, Nur Munevver (Springer Science and Business Media LLC, 2012)
This study concerns the evaluation of micromorphological and anatomical characters of fruit (achene-cypsela) in 12 Turkish endemic Tripleurospermum taxa using multivariate analyses (cluster analysis, principal component analysis, one-way analysis of variance). Pericarp in all taxa examined is mainly composed of several layers of parenchymatous and sclerenchymatous cells with one vascular bundle in each rib. In the achene, the thickness and width of lateral and adaxial ribs with presence or absence of a slime envelope have high taxonomic value for Tripleurospermum at interspecific levels. The slime envelope formation is also correlated with ploidy levels and habitats of some taxa in Tripleurospermum.
Keywords: 15. Life on land